PENGARUH LINGKUNGAN KERJA, KETERLIBATAN KERJA TERHADAP KOMITMEN PEKERJAAN PADA KARYAWAN CAFÉBLUE DOORS DI SURABAYA - Teguh, Puput Febriany (Universitas Widya Kartika Surabaya, 2024)
The increasing number of cafés in Surabaya means that there are many job opportunities and currently all places of work are competing to maintain their business, especially in the café sector, this is one of the zones that experiences high turnover. The researcher intends to analyze the work environment and also work involvement by formulating the problem, namely